Optimalisasi Pojok Literasi Sebagai Sarana Pembelajaran Mandiri Bagi Siswa Sekolah Dasar: (Studi Kasus pada SDN DAON 3) - Muhammad Fazri Romadhon; Muhammad Fadilah Nur Rohman; Novi Diah Haryanti; Lathifah Azahra; Nurhasiah Majid (Lembaga Pengembangan Kinerja Dosen, 2026)
The low reading interest among elementary school students has become one of the major challenges in improving basic literacy quality within the educational environment. To address this issue, the Literacy Corner program was introduced as an engaging and easily accessible facility for students to develop independent learning habits. This community service activity aims to optimize the function of the Literacy Corner at SDN Daon 3 as a medium that promotes self-directed learning and fosters reading habits from an early age. The implementation method employed a participatory approach, involving teachers and students in the process of providing reading materials, organizing the Literacy Corner space, and conducting training sessions on its effective use in learning activities. The program was carried out during the Community Service Program (Kuliah Kerja Nyata / KKN) at SDN Daon 3, Daon Subdistrict, Rajeg District, Tangerang Regency. The results of the activity indicated an increase in students’ reading interest, as reflected in the higher frequency of visits to the Literacy Corner and greater student engagement in independent reading activities. The tangible impact of this initiative was evident in the students’ growing enthusiasm for non-academic reading materials and the school’s positive support. The uniqueness of this program lies in its participatory concept, where students play an active role in managing and developing the book collection, thereby fostering a sense of ownership toward the Literacy Corner. Based on the outcomes of this community service, it is recommended that the school continue to develop literacy activities sustainably, with ongoing support from teachers, parents, and the surrounding community to ensure consistent growth of literacy culture.